2017
DOI: 10.3168/jds.2016-11113
|View full text |Cite
|
Sign up to set email alerts
|

Associations between exposure to bovine herpesvirus 1 (BoHV-1) and milk production, reproductive performance, and mortality in Irish dairy herds

Abstract: As cost-benefit analyses are required to prioritize and promote disease control and eradication programs within a jurisdiction, national data relating to disease-related production losses are particularly useful. The objectives of the current study were to use Irish bovine herpesvirus 1 (BoHV-1) prevalence data in dairy herds, obtained by bulk milk sampling on 4 occasions over the 2009 lactation, to document associations between milk production, fertility performance, mortality, and BoHV-1 herd status. Bulk mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
1
26
0
2
Order By: Relevance
“…Furthermore, Loneregan et al found BoHV-1 immunopositivity in 2 out of 108 acute interstitial pneumonia lungs and 3 out of 50 bronchopneumonia lungs (28). In the present study, more than 50 % BoHV-1 immunopositivity in fibrin bronchopneumonia and interstitial pneumonia cases was associated with predisposition to viral agents and secondary bacterial agents such as pneumonic pasteurellosis (29,30).…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, Loneregan et al found BoHV-1 immunopositivity in 2 out of 108 acute interstitial pneumonia lungs and 3 out of 50 bronchopneumonia lungs (28). In the present study, more than 50 % BoHV-1 immunopositivity in fibrin bronchopneumonia and interstitial pneumonia cases was associated with predisposition to viral agents and secondary bacterial agents such as pneumonic pasteurellosis (29,30).…”
Section: Discussionsupporting
confidence: 59%
“…Another study found that calving intervals were increased by 12% in mature cows that had experienced severe BRD as calves during their first three months [77,78]. In Irish herds with a seasonal calving pattern that were identified as positive by a bulk tank BHV-1 enzyme linked immunosorbent assay (ELISA), the three-week calving rate was significantly lower in multiparous cows in comparison with BHV-1 negative herds [79]. Two related epidemiology studies in Ethiopia found significantly higher rates of uterine infection and retained fetal membranes in cows that were seropositive for BHV-1 [80,81].…”
Section: Bovine Herpesvirus-1mentioning
confidence: 99%
“…La IBR es una patología de gran cuidado y vigilancia en los hatos, puesto que puede causar abortos, afectar los periodos de lactancia y subsecuentemente, los índices productivos y reproductivos, ocasionando notables pérdidas económicas (Ruiz-Sáenz et al 2010;Sayers 2017). En Colombia, la normatividad para la movilización de bovinos no contempla la IBR, por lo que la infección puede diseminarse desde zonas endémicas a libres fácilmente (Montoya et al 2011).…”
Section: Total Hatos Muestreadosunclassified
“…La rinotraqueitis infecciosa bovina, IBR por sus siglas en inglés, es una enfermedad de distribución mundial producida por el virus herpes bovino tipo 1 (VHB-1), perteneciente a la familia Herpesviridae, subfamilia Alphaherpesviridae (Ackermann y Engels 2006). Es una enfermedad viral con alto impacto sobre la salud y productividad del ganado que afecta principalmente el tracto respiratorio y reproductivo (Raaperi et al 2014;Muratore et al 2017;Sayers 2017). Tiene gran impacto económico en los hatos a nivel mundial causando muchos síndromes clínicos en el ganado (Chase et al 2017).…”
Section: Introductionunclassified